A facile growth process of highly single crystalline Ir1−xVxO2 mixed metal oxide nanorods and their electrochemical properties. Issue 25 (13th June 2017) - Chun, Sung Hee; Kim, Hyun Yeong; Jang, Hyesu; Lee, Yejung; Jo, Ara; Lee, Nam-Suk; Yu, Hak Ki; Lee, Youngmi; Kim, Myung Hwa; Lee, Chongmok
Abstract : Single crystalline Ir1− x V x O2 nanorods were grown on an Si wafer as well as on an Au microwire by a vapour transport process. Abstract : We introduce a facile growth process for mixed metal oxide nanorods of Ir1− x V x O2 in the broad range of metal contents between iridium and vanadium via a vapor phase transport process and their electrochemical performance. The growth process of Ir1− x V x O2 nanorods was performed by modulating the ratios of two precursors of VO2 and IrO2, the growth temperature, the position of metal oxide precursors in a furnace, and the flow rate of carrier gases. The results indicated that quasi one-dimensional nanostructures of Ir1− x V x O2 can be obtained of a single crystalline nature with the tetragonal rutile crystal structure by randomly incorporating Ir 4+ and V 4+ metal ions into the same lattice unit of the tetragonal structure owing to similar ionic sizes. In addition, the fundamental electrochemical performances for Ir1− x V x O2 nanorods grown directly on an Au microelectrode of 25 μm in diameter were carefully tested in order to explore the nonenzymatic amperometric sensing capacity of ascorbic acid as a biologically important molecule.